THE USE OF PERSONAL VOCABULARY NOTES TO IMPROVE STUDENTS’ VOCABULARY MASTERY OF SMP NEGERI 3 TOTIKUM BANGGAI KEPULAUAN - Sahmawati; Rita, Ferry; Anggreni, Afrillia (Tadulako University, 2024)
The objective of this research is to find out whether students’ vocabulary mastery is Improve or not through personal vocabulary notes technique. This research is Pre-Experimental method. Data collection Techniques are Pre-test and Post-test. The results of this research showed that there was improvement of students' vocabulary mastery from the difference between the pre-test and post-test is 31.1, The results of the research found that students’ vocabulary this can be seen from the height of the t-conted 88.8 than t-table 1.729. Based on the result, the researcher hopes that the personal vocabulary notes technique can used improve students’ vocabulary mastery of SMP Negeri 3 Totikum